Central Composite Design Aided Formulation Development and Optimization of Clarythromycin Extended-Release Tablets - Pharmacy, Department of Industrial; Education, Raghavendra Institute of Pharmaceutical; (RIPER)-Autonomous, Research; Cross, KR Palli; Chiyyedu, Chiyyedu; Anantapur, Anantapur; Pradesh, Andhra; Pharmacology, INDIA. Department of; INDIA., INDIA. (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: The present work was designed to formulate extended-release tablets of clarithromycin by means of central composite design. To assess the systematic considerate of input and output variables and to construct design space, the central composited design was used. Methods: The concentrations of tamarind kernel powder (X1), ethyl cellulose (X2) and polyvinyl pyrrolidone (X3) remained as independent variables and responses were drug release in 2 h, 8 h and t50%. Polynomial equations were employed to forecast the quantitative result of nondependent constraints at different levels on responses. The model stood nonlinear and the curvature outcome was significant. Henceforth the study employed central composite design for optimization. Wet granulation method was used to prepare the tablets and were evaluated for pharmacotechnical properties. Results: FTIR and DSC studies signposted that drug and excipients were compatible. Precompression constraints specified respectable flow properties. The in vitro drug release of entire formulations at the end of 12 h was found to be 96.14% - 98.23%. Increase in the concentration of tamarind kernel powder, ethyl cellulose decreased percentage drug release. Contour plots were utilized to assess the relationship between independent variables and dependent variables. Conclusion: The statistical model is scientifically effective as the investigational estimates and foreseen estimates proposed by the model were relatively close to each other. The outcomes confirmed the success of the anticipated design for development of clarithromycin extended-release tablets with optimized properties.
Keywords: Tamarind kernel powder; Ethyl cellulose; Polyvinyl pyrrolidone; Clarithromycin; Central composite design; Extended release